2019
DOI: 10.1108/mrr-03-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling, business analytics and big data interpretation

Abstract: Purpose The purpose of this paper is to explore the role of storytelling in data interpretation, decision-making and individual-level adoption of business analytics (BA). Design/methodology/approach Existing theory is extended by introducing the concept of BA data-driven storytelling and by synthesizing insights from BA, storytelling, behavioral research, linguistics, psychology and neuroscience. Using theory-building methodology, a model with propositions is introduced to demonstrate the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 73 publications
(159 reference statements)
1
29
0
Order By: Relevance
“…In the context of business analytics, Boldosova and Luoto (2019) describe data storytelling as a narrative sensemaking heuristic that helps business analytics practitioners to make sense of the big data and guides them though the process of interpreting and translating complex data patterns into a sequence of coherent and meaningful insights, which in turn, can lead to improved decision-making and performance. Similarly, Dykes (2019) defines data storytelling as a structured approach for conveying and communicating insights resulting from the data analysis process in a way that allows the relevant audience to easily and quickly understand the analytical insights, understand the context of these insights, and draw conclusions from them.…”
Section: Data Storytelling In Business Analytics Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of business analytics, Boldosova and Luoto (2019) describe data storytelling as a narrative sensemaking heuristic that helps business analytics practitioners to make sense of the big data and guides them though the process of interpreting and translating complex data patterns into a sequence of coherent and meaningful insights, which in turn, can lead to improved decision-making and performance. Similarly, Dykes (2019) defines data storytelling as a structured approach for conveying and communicating insights resulting from the data analysis process in a way that allows the relevant audience to easily and quickly understand the analytical insights, understand the context of these insights, and draw conclusions from them.…”
Section: Data Storytelling In Business Analytics Practicesmentioning
confidence: 99%
“…Another study by Boldosova (2019) found that the use of data storytelling in combination with big data analytics techniques can improve customers' adoption of services and products and enhance the relationship between organizations and their customers, thereby developing innovative solutions to meet growing market needs and enhancing existing business processes. Recent studies have also emphasized the pivotal role that data storytelling plays in augmenting business analytics initiatives and assisting individuals in interpreting and making sense of complex data patterns and insights (Boldosova & Luoto, 2019). Sharda, Delen, and Turban (2019) argue that when insights generated from business analytics are integrated into compelling stories, organizations can see a marked change in their performance across key areas of the business, such as return on investment (ROI), return on sales (ROS), customer retention and satisfaction, employees' productivity, employees' growth and professional development, and market share (Aydiner, Tatoglu, Bayraktar, Zaim, & Delen, 2019).…”
Section: Data Storytelling Competency and Business Performancementioning
confidence: 99%
See 3 more Smart Citations